The Influence of Sharia Marketing on Investment Decisions in the Sharia Capital Market - Natsir, Imron; Mukaromah, Hajar; Hasirah, Hasirah; Irawaty, Rosalia; Irwin, Andi (Jurnal Economic Resource, 2025)
In Indonesia, the development of the Islamic capital market began in 1997 with the introduction of Islamic mutual funds, initiated by Danareksa. The principles of this Islamic capital market differ from those of conventional capital markets. In this study, the author employed a quantitative approach. This research is part of a study that employs a survey method for data collection. The survey conducted by the researcher in this study used an online questionnaire to collect data from students of the Faculty of Economics at several campuses, resulting in 150 respondents. The population and sample in this study consisted of students from the Faculty of Economics, and the data analysis technique employed was SPSS multiple linear regression. The results of this study indicate that online community interaction, content sharing, and accessibility variables have a significant influence on investment decisions in the Islamic capital market. This suggests that a well-designed engagement strategy plays a crucial role in enhancing investor participation in instruments that adhere to Islamic principles. Meanwhile, the credibility variable has no effect on investment decisions in the Islamic capital market.